Histologic Typing in Oropharyngeal Squamous Cell Carcinoma: A 4-Year Prospective Practice Study With p16 and High-Risk HPV mRNA Testing Correlation. (August 2016) - Gondim, Dikson Dibe; Haynes, Wesley; Wang, Xiaowei; Chernock, Rebecca D.; El-Mofty, Samir K.; Lewis, James S.
Abstract : Oropharyngeal squamous cell carcinomas (OPSCCs) associated with human papillomavirus (HPV) represent a distinct clinical and pathologic entity. The majority of HPV-related OPSCCs have a characteristic nonkeratinizing morphology. This study sought to determine the strength of the association between nonkeratinizing histology and HPV status compared with other squamous cell carcinoma variants in 4 years of routine clinical practice on a high-volume head and neck service. Primary and/or nodal metastatic tumors in all cases of OPSCC from 2010 to 2013 were typed by 1 of 3 head and neck pathologists as keratinizing, nonkeratinizing, nonkeratinizing with maturation, or another defined variant. All were assessed for p16 by immunohistochemistry with a 70% nuclear and cytoplasmic positivity cutoff as part of routine clinical practice. In addition, 70 consecutive cases from 1 year were "audited" for high-risk HPV mRNA by reverse transcription polymerase chain reaction and in situ hybridization. Of the 435 cases, the majority (90%) consisted of 1 of the 3 main types described and the rest (10%) of uncommon variants. Nonkeratinizing morphology had 99.1% and 100.0% positive predictive value for p16 and high-risk HPV mRNA positivity, respectively. Nonkeratinizing with maturation, keratinizing, and other specific squamous cell carcinoma variants were p16 positive in 91.8%, 22.8%, and 79.5%, respectively. All 47 nonkeratinizing OPSCCs tested for HPV mRNA were positive. In summary, strictly defined nonkeratinizing OPSCC (which constitutes ∼55% of all tumors) essentially implies positivity for both p16 and transcriptionally active high-risk HPV.